Histologic features of sublingual gland herniation through the mylohyoid muscle - Kim, Hong Chan (Int J Clin Exp Pathol, 2019)
Objectives/Hypothesis: The purpose of this study was to document histologic features of the herniated sublingual gland (SLG) and investigate the histologic correlation between herniated SLG and plunging ranula. Methods: One hundred half-heads from 50 adult cadavers (21 females and 29 males) were included in this study. The presence of SLG herniation and the histologic features SLG were analyzed. The histologic features were analyzed according to the part: intraoral, junctional, and herniated parts. Hematoxylin and eosin (H&E), periodic acid Schiff reaction (PAS), and Alcian Blue (pH 2.5) staining were performed. Results: SLG herniation was found in 42 of 100 half-heads. Non-herniated SLG and the intraoral part of the herniated SLG were mainly composed of mucous acini and a few mixed acini. Junctional and herniated parts were mainly composed of serous acini and showed fatty change. PAS and Alcian blue staining showed that both acidic and neutral mucinous acini of junctional and herniated parts were decreased. However, there was no pseudo-epithelium at any site of herniation. Conclusions: The histologic features of herniated SLG are different according the portions. The herniated part showed fatty degeneration and the remaining acini were mainly serous. We cannot confer any correlation between plunging ranula and the herniated part of SLGs.